2013
DOI: 10.4238/2013.march.11.9
|View full text |Cite
|
Sign up to set email alerts
|

Conservation genetics of Annamocarya sinensis (Dode) Leroy, an endangered endemic species

Abstract: ABSTRACT. The endangered perennial plant Annamocarya sinensis (Dode) Leroy is a tertiary relict tree restricted to southeastern China and northern Vietnam. To explore endangerment mechanisms, develop protection strategies, and guide reintroduction efforts for this species, we investigated genetic diversity and population structure by surveying 70 individuals from three distinct populations using 12 polymorphic microsatellite markers. We found high genetic diversity for A. sinensis as indicated by high allelic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 31 publications
(28 reference statements)
1
10
0
Order By: Relevance
“…SSRs, and especially expressed sequence tag-SSRS (EST-SSRs), have been widely used in studies of conservation genetics of endangered species, including Annamocarya sinensis (Zhang et al, 2013), Toona ciliata (Liu et al, 2014), Aconitum austrokoreense (Yun et al, 2015), and others. Regarding P. dabeshanensis, Zhang et al (2015) developed 28 polymorphic SSR markers from the transcriptome assembly of the congeneric species P. lambertiana, whereas Xiang et al (2015) identified 19 polymorphic EST-SSRs from a cDNA library of P. dabeshanensis needles.…”
Section: Introductionmentioning
confidence: 99%
“…SSRs, and especially expressed sequence tag-SSRS (EST-SSRs), have been widely used in studies of conservation genetics of endangered species, including Annamocarya sinensis (Zhang et al, 2013), Toona ciliata (Liu et al, 2014), Aconitum austrokoreense (Yun et al, 2015), and others. Regarding P. dabeshanensis, Zhang et al (2015) developed 28 polymorphic SSR markers from the transcriptome assembly of the congeneric species P. lambertiana, whereas Xiang et al (2015) identified 19 polymorphic EST-SSRs from a cDNA library of P. dabeshanensis needles.…”
Section: Introductionmentioning
confidence: 99%
“…Primers were designed using the Primer Premier software (Version 5.0, PREMIER Biosoft) ( Table 2). PCR amplification was performed as reported previously by Zhang et al (2012). GeneMapper ® ID Software(Version 3.2, Applied Biosystems) was used to analyse size peaks.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, to get enough primers for genetic analysis, another 110 SSR markers were also deliberately selected from four different sources: 19 genomic SSR markers (denoted as PM-CIN) were selected from the C. cathayensis developed by Grauke et al (2003); 42 genomic SSRs (denoted as WGA) were from J. nigra, including 14 developed by Dangl et al (2005) and 28 (out of 30, excepted WGA4 and WGA69) developed by Woeste et al (2002); 37 EST-SSRs (denoted as ZMZ and ZY) were from the J. regia developed by Qi et al (2011); and 12 EST-SSRs (denoted as BJF-As) were from the A. sinensis developed by Zhang et al (2012).…”
Section: Ssr Developmentmentioning
confidence: 99%
“…PCR amplification, product separation, and gel staining were performed as reported previously by Zhang et al (2012). The PCR products were resolved using an ABI 3730XL DNA analyzer from Genewiz Biotechnology Co., Ltd. (Beijing, China) and the data were analyzed with the Gene-Marker software (SoftGenetics LLC, Oakwood Ave, PA, USA).…”
Section: Polymerase Chain Reaction (Pcr) Amplificationmentioning
confidence: 99%
See 1 more Smart Citation